Cultural Psychology Of Religion: Profile Of An Interdisciplinary Approach - Belzen, Jacob A. (Research in the social scientific study of religion, 2009)
Cultural psychology and psychology of religion have a good deal in common: being major fields at the inception of psychology, they have become marginalized during the 20th century, but are both returning to the fore in impressive ways. Although there is increasing attention to religion in cultural psychology, the cultural psychological approach is hardly yet applied in psychology of religion. This paper distinguishes three variants in cultural psychology, reviews contemporary research in cultural psychology, and then turns to cultural psychological approaches to the study of religion. The paper points out the interdisciplinary character of cultural psychology of religion, discusses some current cultural psychological theories and their application to religion, and presents a number of examples of recent empirical research projects.